MANAJEMEN KONFLIK DAN TERAPEUTIK JIWA - Sabari (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
The purpose of this study is to describe the other roles of conflict management, one of which is related to mental therapeutic activities. Conflict is basically a process that starts when one party feels displeased by, or there is an intention to do unpleasant to the other party regarding something that is considered by the first party to be important. The result of this research is conflict management and mental therapeutic are activities that are solutive, namely finding ways to resolve and at the same time responding to the soul with the right advice and steps. So it is hoped that research can make a major contribution to the development of da'wah in accordance with the meaning of the da'wah itself, namely conveying virtues. There are several ways that conflict management can have a therapeutic effect on the soul, including: first, integrating (Problem Solving), second, obliging (smoothing), third, dominating (forcing), fourth, avoiding, fifth, compromising.